Global Taxation and National Welfare States - Priyaranjan Jha; Rahul Mukherjee (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the effects of globalization on the ability of governments to generate tax revenues for the financing of national welfare states. In this context, it summarizes the theoretical predictions of various economic models of tax competition between countries and discusses the role of factor mobility and country-specific characteristics such as size and factor abundance. It then draws on existing empirical evidence to outline the effects of globalization on capital, labor and consumption taxes. It touches on recent trends in income tax incentives for highly skilled workers, the challenges related to digital platforms, and ends with a discussion of recent attempts at international tax coordination among countries, including the OECD BEPS initiative.
Keywords: F21; F22; F23; F62; F68; H11; H21; H25; H71; J61; 330; globalization; welfare state; tax competition; corporate taxation; income taxation; global tax coordination